Service Level Agreements in Cloud Computing and Big Data - K. Radha; B.Thirumala Rao; Shaik Masthan Babu; K.Thirupathi Rao; V.Krishna Reddy; P. Saikiran (Institute of Advanced Engineering and Science, 2015)
Now-a-days Most of the industries are having large volumes of data. Data has range of Tera bytes to Peta byte. Organizations are looking to handle the growth of data. Enterprises are using cloud deployments to address the big data and analytics with respect to the interaction between cloud and big data. This paper presents big data issues and research directions towards the ongoing work of processing of big data in the distributed environments.